Faktor Risiko yang Berhubungan dengan Kejadian Hipertensi pada Masyarakat di Wilayah Kerja Puskesmas Krueng Barona Jaya Kabupaten Aceh Besar Tahun 2025 - Ayu Vinezia Situmeang; Tahara Dilla Santi; Farrah Fahdhienie (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Hypertension is a non-communicable disease with the highest prevalence in Indonesia, so it is necessary to conduct research on its risk factors. This study aims to determine the risk factors associated with the incidence of hypertension in the community in the working area of ​​the Krueng Barona Jaya Community Health Center, Aceh Besar Regency in 2025. The type of research is descriptive analytic with a case-control design. The sample consisted of 176 respondents, namely 88 cases and 88 controls, who were selected by random sampling. The study was conducted on August 7–12, 2025 through interviews with a structured questionnaire, and data were analyzed using the chi-square test in SPSS. The results showed that 50.0% of respondents were hypertension cases. A total of 58.0% had consumed caffeine, 55.7% were obese, 33.5% had high physical activity, 58.5% had poor diet, and 47.2% had comorbidities. Bivariate analysis showed a significant relationship between caffeine consumption, BMI, physical activity, diet, and comorbidities with the incidence of hypertension. It is recommended that Community Health Centers strengthen health promotion, cadres increase early screening, and the Health Service support community examination and sports facilities.